PENGEMBANGAN MODEL HEDONIC SEBAGAI ALAT UNTUK MENENTUKAN NILAI JAMINAN TANAH UNTUK KREDIT BANK - Hening Widi Oetomo (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
Hedonic is a model for estimating the land value based on the identified factors that can influence the value of land. There are there (3) factors that influence the value of the land; i.e.; its structure, neighbourhood and location. The current study tries to establish a Hedonic Model that used to determine the land value as guarantee for bank credit. For structure factors, it uses 4 variables, they are the extent of total are, the front width, the direction and the index of the shape. The neighbourhood factors uses 2 variables; i.e.; the number of the sport facilities in radius of 1000 meters and the number of the hospitals in radius of 1250 meters. While the location factor uses 2 variables; i.e.; the nearest distance to the center of the city and the nearest distance to the main road. Statistical analysis used is regression analysis toward land lot sale value of the sample in 2005 as many as 2009 lots.  The analysis result suggest that five variables are significant at the stage of α = 0,05, they are extent, shape index, the number of sport facilities in the radius of 1000 meters, hospital facilities in radius of 1250 meters and the distance to the main road. As a whole, this model is able to explain 59,6% of the land value, while the rest 40,4% is explained by other variables outside this model.Hedonic model, Land value, Structure and Location.